2008
DOI: 10.1590/s0365-05962008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Significado do epitope spreading na patogênese dos pênfigos vulgar e foliáceo

Abstract: Resumo: Os pênfigos são dermatoses bolhosas auto-imunes, em que há a produção de auto-anticorpos direcionados contra moléculas de adesão dos epitélios, levando à perda da coesão celular. A produção de auto-anticorpos ocorre quando os pacientes desenvolvem um desequilíbrio da resposta imune (quebra da tolerância imunológica), passando a reconhecer antígenos próprios. A resposta é geralmente direcionada contra um único epítopo alvo; entretanto, como conseqüência da resposta inflamatória do processo primário e do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…1-3 Acantholysis allows differentiation with the bullous pemphigoid (BP) group, in which the whole epidermis is lost without acantholytic changes.…”
Section: Introductionmentioning
confidence: 99%
“…1-3 Acantholysis allows differentiation with the bullous pemphigoid (BP) group, in which the whole epidermis is lost without acantholytic changes.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of the disease is associated with epitope spreading, in which repeated exposure to insect bites ( Simulium nigrimanum ) would increase the production of pathogenic antibodies of the IgG4 subclass that lead to the recognition of the EC1 and EC2 domains of Desmoglein-1. 55 , 56 During the 20th century, there was a great increase in the incidence of the disease along areas of deforestation in the countryside of Brazil, especially in the states of São Paulo, Mato Grosso, Goiás and Minas Gerais, following large river basins. 57
Figure 2 Fogo selvagem or endemic pemphigus foliaceus.
…”
Section: Environmental Degradationmentioning
confidence: 99%
“…6 Various studies have shown that the circulating antibodies associated with the skin in cases of pemphigus belong predominantly to different IgG classes, particularly IgG1 and IgG4. 7 Of the three variants of pemphigus, the most severe is paraneoplastic pemphigus in view of its association with known or occult malignancy.…”
Section: Introductionmentioning
confidence: 99%